Exploring Indigenous Women’s Dietary Practices with the Women Warriors Program: Social Determinants and Resilience in Seeking Wellness - Sampson, Megan Beth (Arts, 2018)
Indigenous women (First Nation, Métis, and Inuit) experience nutrition-related chronic illness at disproportionate rates when compared to both Indigenous men and the Canadian population at large. Negative social determinants of health stemming from recent and historical injustices contribute to this reality. Indigenous women’s position in Canada is distinct as they may face marginalization on the basis of sex, race, and socioeconomic status. Despite these realities, Indigenous feminist literature demonstrates that Indigenous women are often at the forefront of anticolonial movements and attempts to improve wellness within their communities. This research investigates what Indigenous women’s dietary practices reveal about their distinct experiences, needs, preferences, and values relating to food and health. It took place on Treaty 6 territory in the city of Lloydminster and its surrounding rural areas, and includes the experiences of Cree and Métis women. Current public health initiatives targeting individual behaviours are ill-equipped to respond to the larger socio-political roots of problematic dietary practices in Indigenous contexts. These include colonial assaults on Indigenous food systems which have resulted in trauma, food insecurity, and the transition away from traditional foods toward store-bought, processed alternatives. My intent in conducting this research was to engage Indigenous Women in conversations about how these factors impact them, how they cope with or combat them, and what supports they seek out and offer to others in light of such experiences. Literature relating to social economy and social capital, the social determinants of health, anticolonial theory, Indigenous perspectives of health and wellness, and Indigenous feminism frame findings collected through interdisciplinary ethnographic methods that include participant observation, dietary recalls, supportive network mapping, and personal narratives. Underlying the research design is the recognition that Indigenous women’s voices ...